2022
DOI: 10.1016/j.cpcardiol.2021.100905
|View full text |Cite
|
Sign up to set email alerts
|

Presentation and Outcome of Congenital Heart Disease During Covid-19 Pandemic: A Review

Abstract: Severe Acute Respiratory Syndrome Corona Virus 2 (SARS-COV 2 ) infection is a rapid evolving pandemic with multiple peaks of outbreak and substantial mortality worldwide. It has been proposed that infants are more vulnerable to SARS-COV-2 infection. On the other hand, children with COVID-19 have generally milder disease compared to infected adults and more often presented with gastrointestinal symptoms compared to respiratory ones. Multisystem inflammatory syndrome in children (MIS-c) is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Numerous studies have indicated that viral respiratory infections, including influenza and COVID-19, impose a higher risk of mortality, a longer duration of hospitalization, and more complications and economic costs in patients with CHD than the general population [6,[37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have indicated that viral respiratory infections, including influenza and COVID-19, impose a higher risk of mortality, a longer duration of hospitalization, and more complications and economic costs in patients with CHD than the general population [6,[37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our findings on nearly 50% of subjects presenting severe and critical COVID-19 should be analyzed further. These findings might be due to the impact of CHD on COVID-19 progression, the worsening of the CHD condition itself, the interaction between both conditions, or possible bias caused by the study population of only hospitalized patients ( 33 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, less than 9% developed mild or moderate SARS-CoV-2 post-infectious MIS-C within 4–6 weeks of infection and inflammatory dysfunction of various degrees in multiple systems, such as mucocutaneous, gastrointestinal and cardiovascular, throughout the body ( Fig. 2 B) [72] , [79] , [80] , [81] , [82] . Thirdly, a small amount of patients with severe underlying diseases or moderate MIS-C without timely intervention, deteriorated and eventually progress to severe and critical disease, which included multiple organ failure (MOF) or death.…”
Section: The Clinical Manifestation Of Sars-cov-2 Infected Childrenmentioning
confidence: 99%